Novel silica, process for its preparation and use thereof
Patent Information
- Application Number
- JP2023560562
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-04-02
- Filing Date
- 2022-04-01
- Publication Date
- 2025-04-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing precipitated silica used in polymer and oral care compositions faces challenges with dispersibility and reactivity due to high silanol content, leading to suboptimal performance in elastomer formulations and oral care products.
Heat treatment of precipitated silica at 300-600°C reduces silanol content, improving dispersibility and reactivity, resulting in a silica with a silanol ratio of 0.1-2.5 mmolOH/g and CTAB surface area of 45-350 m²/g, enhancing its use in elastomers and oral care compositions.
The treated silica exhibits improved mixing with elastomers, reduced water uptake, and enhanced adsorption of formulation components, leading to better performance in elastomeric compositions and oral care products.
Abstract
Description
[Technical field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims priority to European Patent Application No. 21305429.9, filed April 2, 2021, the entire contents of which are incorporated herein by reference for all purposes.
[0002] The present invention relates to a novel silica, a process for the preparation of said silica, and its uses. [Background technology]
[0003] Silica has long been used as a reinforcing filler in polymeric materials, especially elastomers, and has also been widely used in oral care compositions (toothpastes) due to its ability to act as a thickener (facilitating the formation of a gel by absorbing water).
[0004] It has now been found that heat treating (calcining) silica, particularly precipitated silica, improves the use of said precipitated silica in polymer compositions, which also improves the use of said precipitated silica in oral care compositions.
[0005] That is, it has been found that the silica according to the invention is easy to mix with elastomers, allowing an improved method for the preparation of elastomeric compositions containing well-dispersed silica. The silica according to the invention also has low water absorption and a low density of silanol functional groups that affect reactivity in elastomeric formulations. This also provides improved oral care compositions.
[0006] More precisely, it has been found that heat treatment of silica, especially in its final form (such as microbeads), changes its surface reactivity towards silanes and elastomers, affecting the adsorption of other components of the formulation (e.g. accelerators), and it also changes the surface reactivity with other components of the oral care composition. Summary of the Invention
[0007] Thus, the present invention provides CTAB surface area is 45m 2 / g over ~350m 2 / g; and Silanol ratio T SiOH is 0.1 to 2.5 mmol OH / g; The present invention relates to a precipitated silica characterized in that
[0008] The first embodiment of the present invention is CTAB surface area is 100~350m 2 / g; and Silanol ratio T SiOH is 0.1 to 2.5 mmol OH / g; The present invention relates to a precipitated silica characterized in that
[0009] A second embodiment of the present invention is CTAB surface area is 45m 2 / g over ~100m 2 / g; and Silanol ratio T SiOH is 0.1 to 2.5 mmol OH / g; The present invention relates to a precipitated silica characterized in that
[0010] The term "silica" is used herein to refer to silicon dioxide, SiO2. The term "silica" is used throughout the text to refer to precipitated silica. The term "precipitated silica" is used to refer to synthetic amorphous silica obtained by the process of reacting silicates with acids to precipitate SiO2.
[0011] The silica of the invention is characterized by a silanol ratio between 0.1 and 2.5 mmol OH / g. Preferably, this ratio is at least 0.5, more preferably at least 0.8 mmol OH / g. Preferably, it is between 0.5 and 2.5, more preferably between 0.8 and 2.5 mmol OH / g.
[0012] Silanol ratio (mmol / g) or T SiOHis defined as follows: T SiOH = ΔW * 2 * 1000 / (18.015 * 100) = 1.11 * ΔW (wherein ΔW (%) is the mass loss (%) between 200 ° C and 800 ° C measured by ATD-ATG, preferably as described in detail in the Examples).
[0013] The silica of the present invention is generally 2 The number of OH groups per surface area is expressed as 2OH / nm 2 More than 4OH / nm 2 The number of OH groups per surface area is usually 11OH / nm 2 Less than 10 OH / nm 2 The silica of the present invention advantageously has a number of OH groups per surface area of 2 to 11 OH / nm 2 It is characterized by being.
[0014] The determination of the silanol ratio and the number of OH groups per surface area is determined using the ATD-ATG technique detailed below.
[0015] In a first embodiment of the present invention, the CTAB surface area is at least 100 m 2 / g, typically at least 120m 2 / g. The surface area of CTAB is 150 m 2 In this embodiment, the CTAB surface area may be greater than 350 m 2 / g, and the CTAB surface area is preferably 300 m 2 / g or less, and even 250m 2 / g or less, more preferably 200m 2 In this first embodiment, the CTAB surface area is preferably 120 to 300 m 2 / g, more preferably 150 to 250 m 2 / g.
[0016] CTAB surface area is a measure of the external specific surface area determined by measuring the amount of N-hexadecyl-N,N,N-trimethylammonium bromide adsorbed on the silica surface at a given pH. CTAB surface area can be determined according to standard NF ISO 5794-1, Appendix G (June 2010).
[0017] The BET surface area S of the silica of the present invention BET is not particularly limited.
[0018] The BET surface area is determined according to the Brunauer-Emmett-Teller method described in The Journal of the American Chemical Society, Vol. 60, page 309, February 1938, and corresponding to standard NF ISO 5794-1, Appendix D (June 2010).
[0019] The silica of the present invention usually has a BET / CTAB ratio of 0.8 to 1.6, preferably 0.9 to 1.3, and more preferably 1.0 to 1.2.
[0020] Further preferred properties of the silica microparticles relate to their particular shape and size. That is, the silica of the present invention preferably comprises microspheres (micropearls) having an average diameter (measured by SEM) of at least 80 μm. More specifically, this average diameter may be greater than 150 μm, preferably in the range of 200-300 μm. Preferably, the silica of the present invention essentially consists of such micropearls. That is, typically 85% of the weight of the silica microparticles are micropearls, preferably at least 90%, more preferably at least 95% are such micropearls.
[0021] Such micropearls typically comprise aggregates (ie aggregates of smaller particles which are chemically bonded together) having a median particle size d50 measured by centrifugal sedimentation of 80-120 nm, preferably 90-110 nm.
[0022] A further object of the present invention is a process for the preparation of the precipitated silica of the invention, said process comprising the steps of providing a starting precipitated silica (hereinafter defined as "starting silica"); and subjecting the starting precipitated silica to a heat treatment at a temperature between 300 and 600° C., Includes. It was found that temperatures below 300°C had no significant effect, while temperatures above 600°C deteriorated the silica structure, causing problems with dispersibility.
[0023] The starting silica may be in any form such as a powder, granules or substantially spherical beads, the latter being preferred, and more preferred being micropearls (microspheres), preferably as described above. It should be understood that this starting silica is usually a solid (precipitated silica) obtained by precipitating the silica in an aqueous medium using a silicate source (e.g. sodium silicate) and an acid (e.g. sulfuric acid), separating the solid so obtained from the aqueous phase in which it is suspended, and then drying it usually by, for example, spray drying.
[0024] The starting silica is usually characterized by a silanol ratio greater than 2.5.
[0025] Additionally or alternatively, the starting silica typically has a molecular weight of 12 OH / nm 2 Larger, e.g., about 13 OH / nm 2 It is characterized by the number of OH groups per surface area.
[0026] The heat treatment of the present invention is calcination, i.e. heating a solid compound (i.e. starting silica) to high temperatures (i.e. 300-600°C) in a gas or inert atmosphere while keeping it below its melting point. Calcination in the presence of air gives good results within the scope of the present invention. The heat treatment (calcination) can be carried out using any suitable equipment. Non-limiting examples of equipment suitable for heat treatment are for example rotary ovens or muffle furnaces.
[0027] In a further embodiment, the process for the preparation of the modified silica comprises: heating the starting silica to a temperature of 300-600°C; - maintaining the starting silica at a temperature of 300-600°C for 1-150 minutes; cooling the resulting precipitated silica; Includes.
[0028] The heat treatment is preferably carried out at a temperature of 300 to 550°C, more preferably at a temperature of 350 to 500°C.
[0029] The duration of the heat treatment is adjusted so that the silanol ratio decreases from its initial value to a value of up to 2.5 mmol OH / g, which is usually between 1 and 180 minutes. The precipitated silica is preferably kept at the heat treatment temperature for 30 to 150 minutes, preferably for 30 to 120 minutes.
[0030] Any silica can be used as starting silica in the process of the present invention, for example the following commercially available precipitated silicas: Zeosil® 1165MP, Zeosil® 1115MP, Zeosil® Premium 200MP, Zeosil® 195HR, Zeosil® 165GR, Zeosil® 115GR, Zeosil® HRS 1200MP, Zeosil® 195GR, Zeosil® 185GR, Zeosil® 175GR, Zeosil® 125GR (all commercially available from Solvay), Ultrasil® 5000GR, Ultrasil® 7000GR, Ultrasil® 9000GR, Ultrasil® VN3GR, Hi-Sil® EZ 160G-D, Hi-Sil® EZ 150G, Hi-Sil® 190G, Hi-Sil® 200G-D, Hi-Sil® HDP-320G, Hi-Sil® 255CG-D, Zeopol® 8755LS, Zeopol® 8745, Newsil® 115GR, Newsil® 2000MP, Tokusil® 315. They can also be made from silica doped with metals, for example Al, Zr, B, Ga, Sc, Y, Ti, Zr, Hf, Zn, Fe, Cu.
[0031] In particular, non-limiting examples of suitable methods for the preparation of precipitated silicas which may be used as starting silica in the process of the present invention are described, for example, in EP 396450 A, EP 520862 A, EP 647591 A, EP 670813 A, EP 670814 A, EP 901986 A, EP 762992 A, EP 762993 A, EP It is disclosed in Publication No. 917519A, European Patent Application Publication No. 983966A, European Patent Application Publication No. 1355856A, International Publication No. 03 / 016215, International Publication No. 2009 / 112458, International Publication No. 2011 / 117400, International Publication No. 2018 / 202752, International Publication No. 2018 / 202755, International Publication No. 2018 / 202756, and International Publication No. 2020 / 094714.
[0032] The inventive silica according to the invention or obtainable by the process according to the invention described above can be used in many applications.
[0033] The modified silica of the present invention can be used especially as a filler for polymer compositions, especially in elastomeric compositions.
[0034] The polymer compositions which can be used therein, in particular as reinforcing fillers, are usually based on one or more polymers or copolymers, in particular one or more elastomers, preferably exhibiting at least one glass transition temperature between -150°C and +300°C, for example between -150°C and +20°C.
[0035] The expression "copolymer" is used herein to refer to a polymer that contains repeat units derived from at least two monomeric units of different nature.
[0036] Among the possible polymers, particular mention may be made of diene polymers and copolymers, especially diene elastomers.
[0037] For example, polymers or copolymers derived from aliphatic or aromatic monomers containing at least one unsaturation (such as, inter alia, ethylene, propylene, butadiene, isoprene, styrene, acrylonitrile, isobutylene or vinyl acetate), polybutyl acrylate, or mixtures thereof may be used; functionalized elastomers, i.e., elastomers functionalized by chemical groups arranged along the polymer chain and / or at one or more of its ends (for example, by functional groups capable of reacting with the surface of the silica), as well as halogenated polymers may also be mentioned. Polyamides, ethylene homopolymers and copolymers, propylene homopolymers and copolymers may also be mentioned.
[0038] The polymer(co)polymer may be a bulk polymer(co)polymer, a polymer(co)polymer latex, or may be a solution of the polymer(co)polymer in water or any other suitable dispersing liquid.
[0039] Among the diene elastomers, mention may be made, for example, of polybutadiene (BR or butadiene rubber), polyisoprene (IR or isoprene rubber), butadiene copolymers, isoprene copolymers or mixtures thereof, in particular styrene / butadiene copolymers (SBR, in particular ESBR (emulsion) or SSBR (solution)), isoprene / butadiene copolymers (BIR), isoprene / styrene copolymers (SIR), isoprene / butadiene / styrene copolymers (SBIR), ethylene / propylene / diene terpolymers (EPDM). Good results are obtained with SSBR, preferably mixtures with BR.
[0040] Mention may also be made of natural rubber (NR) and epoxidized natural rubber (ENR), with particularly good results being obtained with NR, since the processing of this type of elastomer involves high shear rates.
[0041] The polymeric compositions may be sulfur vulcanized or crosslinked, among others, with peroxides or other crosslinking systems such as diamines or phenolic resins.
[0042] Generally, the polymer composition further comprises at least one (silica / polymer) coupling agent and / or at least one coating agent, which may further comprise, inter alia, an antioxidant.
[0043] Non-limiting examples of suitable coupling agents are, for example, "symmetric" or "asymmetric" silane polysulfides; more specifically, bis((C1-C4)alkoxyl(C1-C4)alkylsilyl(C1-C4)alkyl) polysulfides (particularly disulfides, trisulfides or tetrasulfides), such as bis(3-(trimethoxysilyl)propyl) polysulfide or bis(3-(triethoxysilyl)propyl) polysulfide, for example triethoxysilylpropyl tetrasulfide. Mention may also be made of monoethoxydimethylsilylpropyl tetrasulfide. Mention may also be made of silanes containing masked or free thiol functions.
[0044] The coupling agent can be pre-grafted to the polymer. It can also be used in free form or grafted to the surface of the silica. The same applies to the optional coating agent.
[0045] The weight proportion of the silica of the invention in the polymer composition can vary within fairly wide limits. It usually represents from 10% to 200% by weight relative to the amount of polymer (i.e. from 10 to 200 phr or per 100 rubbers). In particular, when silica is used as the main filler, it is from 20% to 150% by weight relative to the amount of polymer (i.e. from 20 to 150 phr), and when used in combination with a significant amount of carbon black (for example more than 10 phr), it is from 10% to 50% by weight relative to the amount of polymer (i.e. from 10 to 50 phr).
[0046] The inventive silica according to the invention may advantageously constitute all of the reinforcing inorganic filler, and even all of the reinforcing filler, of the polymer composition.
[0047] However, the inventive silica according to the invention can optionally be combined with at least one other reinforcing filler, such as in particular treated precipitated silica (for example precipitated silica "doped" with cations such as aluminum); another reinforcing inorganic filler, for example alumina, or even a reinforcing organic filler, in particular carbon black (optionally coated with an inorganic layer, for example silica).
[0048] The present invention also relates to a polymer composition as described above, i.e. a polymer composition which also comprises the inventive silica as described above.
[0049] These polymer compositions can be used for the manufacture of at least a part of many articles. Non-limiting examples of finished products that comprise at least one of the above-mentioned polymer compositions are, for example, shoe soles, flooring, gas barriers, flame retardant materials, and also engineering parts, such as rollers for aerial cables, seals for household appliances, seals for liquid or gas piping, brake system seals, pipes (flexible), sheaths (especially cable sheaths), cables, engine supports, battery separators, conveyor belts, transmission belts, or preferably tires, especially tire treads (especially for light or heavy vehicles, such as trucks).
[0050] The precipitated silicas of the present invention may also be used as abrasives and / or thickeners in oral care formulations, particularly oral care compositions which contain peroxide-releasing compounds.
[0051] The expression "peroxide-releasing compound" is used herein to refer to hydrogen peroxide, peroxide, and any compound capable of releasing hydrogen peroxide under the conditions of use in oral care applications.Notable non-limiting examples of peroxide-releasing compounds include hydroperoxides, hydrogen peroxide, alkali and alkaline earth metal peroxides, organic peroxy compounds, peroxy acids, their pharma-ceutically acceptable salts, and mixtures thereof.Alkaline and alkaline earth metal peroxides include lithium peroxide, potassium peroxide, sodium peroxide, magnesium peroxide, calcium peroxide, barium peroxide, and mixtures thereof.Organic peroxy compounds include urea peroxide, glyceryl hydrogen peroxide, alkyl hydrogen peroxide, dialkyl peroxide, alkyl peroxy acid, peroxy ester, diacyl peroxide, benzoyl peroxide, monoperoxyphthalate, and mixtures thereof. Peroxyacids and their salts include organic peroxyacids such as alkylperoxyacids, monoperoxyphthalates, and mixtures thereof, and inorganic peroxyacid salts such as alkali and alkaline earth metal perborates, such as lithium, potassium, sodium, magnesium, calcium, and barium, and mixtures thereof. Preferred solid peroxides are sodium perborate, urea peroxide, and mixtures thereof.
[0052] The peroxide-releasing compound may be bound to a polymer, such as a polymer of poly(vinylpyrrolidone), polyacrylate, polymethacrylate.
[0053] Oral care compositions typically contain from 1 to 50% by weight of the peroxide-releasing compound, typically from 3 to 40% by weight, preferably from 3 to 20% by weight.
[0054] The oral care composition contains from 3 to 60% by weight, typically from 5 to 50% by weight, preferably from 5 to 30% by weight of the silica of the invention.
[0055] The compositions of the invention may also contain other ingredients commonly used in oral care applications, in particular other water-insoluble inorganic abrasives, thickeners, humectants, surfactants, etc. Other abrasives that may be mentioned in particular are calcium carbonate, hydrated alumina, bentonite, aluminum silicate, zirconium silicate, and the sodium, potassium, calcium and magnesium metaphosphates and phosphates.
[0056] Among the thickening agents, mention may be made in particular of xanthan gum, guar gum, carrageenan, cellulose derivatives and alginates, the amount of which may range up to 5% by weight of the composition.
[0057] Examples of the moisturizing agent include glycerol, sorbitol, polyethylene glycol, polypropylene glycol, and xylitol, and the amount thereof is about 2 to 85%, preferably about 10 to 70%, of the weight of the composition expressed in dry weight.
[0058] The compositions of the present invention may additionally contain surfactants, detergents, colorants, bactericides, fluoride derivatives, opacifiers, sweeteners, anti-tartar and anti-plaque agents, sodium bicarbonate, preservatives, enzymes, and the like.
[0059] In a preferred embodiment of the present invention, the composition further comprises an antibacterial agent. Notable non-limiting examples of suitable antibacterial agents are chlorhexidine and chlorhexidine salts such as bigluconate or diacetate, triclosan, cetylpyridinium chloride, benzalkonium chloride, and cetyltrimethylammonium bromide.
[0060] To the extent that the disclosure of any patents, patent applications, and publications incorporated herein by reference conflicts with the statements of this application to the extent that it may render a term unclear, this statement shall control.
[0061] The invention will now be described in more detail with reference to the following examples, the purpose of which is merely illustrative and not intended to limit the scope of the invention.
[0062] Analysis method The physicochemical properties of the silica of the invention were determined using the methods described below.
[0063] Determination of CTAB surface area CTAB surface area values were determined according to the internal method taken from standard NF ISO 5794-1, Appendix G.
[0064] BET surface area determination BET surface area S BET was determined according to the Brunauer-Emmett-Teller method detailed in the standard NF ISO 5794-1, Appendix E (June 2010) with the following adjustment: the sample was pre-dried at 200°C ± 10°C and the partial pressure P / P used for the measurement 0 was in the range of 0.05 to 0.3.
[0065] Determination of silanol ratio and silanol density Samples (stored in a dry controlled atmosphere or preconditioned at 105 °C for at least 2 h to eliminate moisture uptake) were analyzed using ATD-ATG technique on a Mettler LF1100 thermobalance and a Tensor27 Bruker spectrometer equipped with a gas cell using the following program: temperature ramp from 25 °C to 1100 °C at 10 °C / min under air (60 mL / min) in 150 μL Al2O3 crucibles. The silanol density is directly related to the mass loss between 200 °C and 800 °C. The mass loss (%) between 200 °C and 800 °C is identified as ΔW%. The silanol ratio (mmol / g) is T SiOH =ΔW*2*1000 / (18.015*100)=1.11*ΔW is defined as follows: Silanol density (OH / nm 2 )teeth, D=T SiOH *Na / 10 21 *S BET =T SiOH *602.2 / S BET where Na is Avogadro's number.
[0066] Determination of particle size distribution and particle size by centrifugal sedimentation in a disc centrifuge (CPS) The d50 values were determined by centrifugal sedimentation in a disk centrifuge using a centrifugal photosedimentometer type "CPS DC 24000UHR" sold by CPS Instruments Inc. The instrument was equipped with operating software provided with the device (operating software version 11g).
[0067] Instrumentation used: For the measurement requirements, the following materials and products were used: Ultrasonic equipment: 1500W generator type Sonics Vibracell VC1500 / VCX1500 with 19mm probe (Converter: CV154 + Booster (Part number: BHNVC21) + 19mm probe (Part number: 630-0208)).
[0068] Analytical balance with 0.1 mg accuracy (e.g. Mettler AE260); syringes: 1.0 ml and 2.0 ml, 20 ga needle; 50 mL tall profile glass beaker (SCHOTT DURAN: diameter 38 mm, height 78 mm); magnetic stirrer with a 2 cm magnetic stir bar; container for ice bath during sonication. Chemicals: deionized water; ethanol 96%; sucrose 99%; dodecane, all from Merck; PVC reference standards from CPS Instrument Inc.; the peak maximum of the reference standards used should be between 200-600 nm (e.g., 237 nm).
[0069] Sedimentation in a disc centrifuge (CPS) For the measurements the following parameters were set: For the calibration standard parameters, the PVC standard information provided by the supplier was used.
[0070] [Table 1]
[0071] Device configuration The measurement wavelength was set to 405 nm. The following runtime option parameters were set:
[0072] [Table 2]
[0073] All other options in the software were left as set by the instrument manufacturer.
[0074] Preparation of the disc centrifuge Spin the centrifuge disks at 24000 rpm for 30 min. Prepare a density gradient of sucrose (CAS n° 57-50-1) as follows:
[0075] In a 50 mL beaker, prepare a 24% by weight solution of sucrose in water. In a 50 mL beaker, prepare an 8% by weight solution of sucrose in water. After homogenizing these two solutions separately, use a 2 mL syringe to take a sample from each solution and inject it into the rotating disc in the following order: Sample 1: 1.8 mL of 24 wt% solution Sample 2: 1.6 mL of 24 wt% solution + 0.2 mL of 8 wt% solution Sample 3: 1.4 mL of 24 wt% solution + 0.4 mL of 8 wt% solution Sample 4: 1.2 mL of 24 wt% solution + 0.6 mL of 8 wt% solution Sample 5: 1.0 mL of 24 wt% solution + 0.8 mL of 8 wt% solution Sample 6: 0.8 mL of 24 wt% solution + 1.0 mL of 8 wt% solution Sample 7: 0.6 mL of 24 wt% solution + 1.2 mL of 8 wt% solution Sample 8: 0.4 mL of 24 wt% solution + 1.4 mL of 8 wt% solution Sample 9: 0.2 mL of 24 wt% solution + 1.6 mL of 8 wt% solution Sample 10: 1.8 mL of 8 wt% solution
[0076] Before each injection into the disk, the two solutions are homogenized in the syringe by adding about 0.2 mL of air and then by short manual stirring for a few seconds, without losing any liquid.
[0077] These injections, the total volume of which is 18 mL, aim to create a density gradient that is useful to eliminate certain instabilities that may appear during the injection of the samples to be measured. To protect the density gradient from evaporation, 1 mL of dodecane is added into the rotating disc using a 2 mL syringe. The disc is then left to rotate at 24000 rpm for 60 minutes before any first measurement.
[0078] Sample preparation 3.2 g of silica was weighed into a 50 mL tall glass beaker (SCHOTT DURAN: diameter 38 mm, height 78 mm) and 40 mL of deionized water was added to obtain an 8 wt % suspension of silica.
[0079] The suspension was stirred on a magnetic stirrer (minimum 20 seconds) before placing the beaker in a crystallizing dish filled with ice and cold water. The magnetic stirrer was removed and the crystallizing dish was placed under an ultrasonic probe placed 1 cm from the bottom of the beaker. The ultrasonic probe was set to 56% of its maximum amplitude and activated for 8 minutes. At the end of sonication, the beaker was placed back on a magnetic stirrer with a 2 cm magnetic stir bar stirring at a minimum of 500 rpm until after sample extraction.
[0080] The ultrasonic probe must be in good working condition. The following inspection must be carried out and in case of unfavourable results a new probe should be used: visual inspection of the physical integrity of the end of the probe (roughness depth less than 2 mm measured with fine calipers); the measured d50 of the commercial silica Zeosil® 1165MP should be 96 nm ± 3 nm).
[0081] analysis Before analyzing each sample, a calibration standard was recorded. In each case, 0.1 mL of a PVC standard was injected, provided by CPS Instruments, whose characteristics were entered in advance into the software. It is important to start the measurement in the software simultaneously with this first injection of the PVC standard. The instrument must be verified before injecting 100 μL of pre-sonicated sample by ensuring that the measurement is started simultaneously upon injection.
[0082] These injections were performed with two clean 1 mL syringes.
[0083] At the end of the measurement, when the time required to settle all particles of smaller diameter (configured in the software to be 0.02 μm) is reached, the ratio of each diameter class is obtained. The curve obtained is called the aggregate size distribution.
[0084] Results: The D50 value is based on a distribution plotted on a linear scale. The integration of the particle size distribution function of the diameters makes it possible to obtain the "cumulative" distribution, i.e. the total mass of particles between the minimum diameter and the diameter of interest. D50 is the diameter below and above which 50% of the mass of the population is. d50 is called the median size of the silica aggregates, i.e. the diameter.
[0085] Example 1 - Preparation of modified silica The modified precipitated silica was prepared according to the following procedure: The starting silica was calcined in air in a muffle furnace according to the following protocol: a 2-10° / min temperature ramp, then a 2-h plateau at the desired temperature, followed by natural cooling (approximately 6-8 h). The properties of the starting silicas (i.e. Zeosil® 1165MP and Premium SW) and the modified silicas using them as starting silicas (i.e. Silicas A to F based on Zeosil® 1165MP and Silicas G to I based on Premium SW) are summarized in Table 1 below.
[0086] [Table 3]
[0087] Table 1 shows that the morphology (particle size and BET) of the silica is not significantly affected by calcination (except for silica F, which was calcined at 650° C.), but the silanol number (i.e., silanol density) is.
[0088] Example 2: Use of Silica in Elastomer Compositions raw materials The silicas according to the invention were evaluated in a NR / BR matrix. The compositions, expressed as parts by weight per 100 parts of elastomer (phr), are given in Table 2 below. The amount of silica (phr) is slightly higher for the reference silica than for the corresponding pyrogenic silica, due to the lower water content of the latter. That is, the amount of silica in phr was adjusted as a function of the water content of the silica to obtain the same amount of SiO2 in the compound.
[0089] [Table 4]
[0090] Process for preparing a rubber composition The preparation of the rubber composition was carried out in two successive preparation stages: a first stage of high temperature thermomechanical processing, followed by a second stage of mechanical processing at a temperature below 110°C to introduce the vulcanization system.
[0091] The first stage was carried out using a Brabender brand internal mixer type mixing apparatus (380 mL capacity). The initial temperature and rotor speed were set to give a mixture temperature of approximately 160°C.
[0092] In the first pass of the first stage, the elastomer and reinforcing fillers (added in portions) were mixed with the coupling agent, carbon black, and stearic acid, the duration being 4 minutes 30 seconds.
[0093] After cooling the mixture (to a temperature below 100° C.), a second pass was made to incorporate the zinc oxide and the protectants / antioxidants, the duration of which was 4 minutes.
[0094] After cooling the mixture (temperature below 100° C.), the vulcanization system (sulfur and accelerator, e.g. CBS) was added during the second stage, which was carried out on an open mill preheated to 50° C. The duration of this stage was 4-6 minutes.
[0095] Each final mixture was then calendered into a plate form with a thickness of 2-3 mm.
[0096] Properties of the vulcanizate The measurements were carried out after vulcanization at 150°C.
[0097] The measurement of mass loss due to abrasion was carried out according to the instructions of NF ISO 4649. The measured value is the volume loss of the material after abrasion (mm 3 ) and the smaller the value, the better the wear resistance.
[0098] The energy dissipation was measured. The loss factor (tan δ) was determined for vulcanized samples (cylindrical samples, cross section 95 mm 2 The measurements were recorded at a temperature of 10° C., height 14 mm. The samples were subjected to a pre-strain with a sinusoidal deformation of 10% and a dynamic solicitation of 4%. The measurements are carried out at 60° C. and a frequency of 10 Hz using a Metravib VA3000.
[0099] The results are summarized in Table 3 below.
[0100] [Table 5]
[0101] The pyrogenic silica according to the invention therefore enables better wear resistance of the compound compared to the starting (non-pyrogenic) silica (similar or better energy dissipation at 60° C.) without adversely affecting the rolling resistance.
[0102] Example 3: Use of Silica in Elastomer Composite Materials The silicas according to the invention were evaluated in an SBR / BR matrix, the compositions expressed as parts by weight per 100 parts of elastomer (phr) being given in Table 4 below.
[0103] [Table 6]
[0104] Process for preparing a rubber composition The preparation of the rubber composition was carried out in two successive preparation stages: a first stage of high temperature thermomechanical processing, followed by a second stage of mechanical processing at a temperature below 110° C. to introduce the vulcanization system. The first stage was carried out using a mixing device of the Brabender brand internal mixer type (volume of 380 mL).
[0105] In the first pass of the first stage, the elastomer and reinforcing filler (introduced in portions) were mixed with the coupling agent, plasticizer, stearic acid, 6-PPD, and ZnO, the duration was 4 minutes 30 seconds, and the drop temperature was about 160°C.
[0106] After the mixture had cooled (to a temperature below 100° C.), the vulcanization system was added during a second stage, which was carried out on an open mill preheated to 50° C. The duration of this stage was 2 to 6 minutes. Each final mixture was then calendered into plaques of thickness 2 to 3 mm.
[0107] Properties of the vulcanizate The measurements were carried out after vulcanization at 160°C.
[0108] After crosslinking, the Z value was measured according to ISO 11345, according to the method described by S. Otto et al. in Kautschuk Gummi Kunststoffe, 58 Jahrgang, NR 7-8 / 2005.
[0109] The percentage of "undispersed area" is calculated using a camera observing the surface of the sample with light incidence at 30°. The bright spots are associated with charges and aggregates, the dark spots with the rubber matrix. Digital processing converts the image into a black and white image, which allows the percentage of "undispersed area" to be determined, as described by S. Otto in the abovementioned publication. The higher the Z value, the better the distribution of the charges within the elastomer matrix (a Z value of 100 corresponds to perfect distribution, a Z value of 0 corresponds to very poor distribution).
[0110] The calculation of the Z value is based on the percentage of the area where the charge is not distributed according to the formula: Z=100-(percentage of undistributed area) / 0.35, as measured by a DisperGrader® 1000 instrument with operating mode and operating software DisperData from Dynisco.
[0111] The results are summarized in Table 5 below.
[0112] [Table 7]
[0113] Silica calcined at 650°C exhibits inferior dispersibility compared to silica calcined at 500°C.
Claims
1. ・CTAB surface area is 45m 2 / g or more than 350m 2 / g; and Silanol ratio T SiOH is 0.1 to 2.5 mmol OH / g; Precipitated silica characterized by:
2. - CTAB surface area is 100 to 350 m2 / g; and - silanol ratio is 0.1 to 2.5 mmolOH / g; 2. The precipitated silica according to claim 1, characterized in that
3. The number of OH groups per surface area is 2 to 11 OH / nm 2 2. Precipitated silica according to claim 1, characterized in that it is
4. 2. Precipitated silica according to claim 1, characterized in that it comprises micropearls having a mean diameter of at least 80 μm.
5. 5. Precipitated silica according to claim 4, characterized in that the micropearls comprise agglomerates with a median particle size d50, measured by centrifugal sedimentation, between 80 and 120 nm.
6. 2. A process for the preparation of precipitated silica according to claim 1, said process comprising the steps of: providing a starting precipitated silica, and subjecting said starting precipitated silica to a heat treatment at a temperature between 300 and 600° C., A method comprising:
7. 7. The method of claim 6, wherein the starting precipitated silica comprises micropearls.
8. heating the starting precipitated silica to a temperature of from 300 to 600°C; - holding the starting precipitated silica at a temperature of 300-600°C for 1-150 minutes; and - cooling the precipitated silica obtained; The method of claim 6, comprising:
9. 10. Use of the precipitated silica according to claim 1 or obtainable by the process according to claim 6 as a filler for polymer compositions, in particular elastomeric compositions.
10. 10. The use according to claim 9, wherein the polymer composition comprises a diene polymer or copolymer, in particular a diene elastomer.
11. 11. Use according to claim 10, wherein the polymer composition comprises styrene / butadiene copolymer (SBR), i.e. SSBR, preferably polymerized in solution, natural rubber (NR), and / or epoxidized natural rubber (ENR), more preferably NR.
12. The use according to claim 11, wherein the polymer composition also comprises butadiene rubber (BR).
13. A polymer composition comprising the precipitated silica according to claim 1 or the precipitated silica obtainable by the process according to claim 6.
14. Finished products comprising the polymer composition according to claim 13 selected from shoe soles, flooring, gas barriers, flame retardant materials, also engineering parts such as rollers for aerial cables, seals for household appliances, seals for liquid or gas piping, brake system seals, pipes (flexible), sheaths (especially cable sheaths), cables, engine supports, battery separators, conveyor belts, transmission belts or (parts of) tires, preferably tires.
15. 15. The finished article of claim 14 which is at least a portion of a tire tread for a light or heavy vehicle, such as a truck.
16. - CTAB surface area is greater than 45 m2 / g and less than 100 m2 / g; and Silanol ratio T SiOH is 0.1 to 2.5 mmol OH / g; 2. The precipitated silica according to claim 1, characterized in that
17. 10. Use of the precipitated silica according to claim 1 or obtained by the method according to claim 6 in oral care formulations, preferably as an abrasive and / or thickener, in particular in oral care compositions comprising a peroxide-releasing compound.